A threshold authenticated encryption scheme using hybrid problems - Mohamad, Mohd Saiful Adli; Ismail, E. S. (Hikari Ltd, 2014)
In this paper, we propose a threshold authenticated encryption scheme using both factoring and discrete logarithm problems.We apply the concept of threshold cryptography in the verification and message recovery phase, where t out of n recipients are required to verify and recover the message. Security analysis shows that our scheme will remain secure even if one of these problems can be solved.